2017
DOI: 10.1097/mat.0000000000000486
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation of Artificial Heart Muscle: A Look Into the Electrophysiologic and Genetic Implications

Abstract: Development of tissue-engineered hearts for treatment of myocardial infarction or biological pacemakers has been hindered by the production of mostly arrhythmic or in-synergistic constructs. Electrical stimulation (ES) of these constructs has been shown to produce tissues with greater twitch force and better adrenergic response. In order to further our understanding of the mechanisms underlying the effect of ES, we fabricated a bioreactor capable of delivering continuous or intermittent waveforms of various ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…It has been shown that this ISI needs to be less than 10 ms and greater than 6 ms to meet the safety requirements of biphasic stimulation. 47 The aim of adding ISI into the cathodal-first stimulation waveform is to reduce the threshold strength of the following anodal stimulation. 47 However, to guarantee the safety of stimulation, the interval between cathodal and anodal stimuli cannot be too large.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that this ISI needs to be less than 10 ms and greater than 6 ms to meet the safety requirements of biphasic stimulation. 47 The aim of adding ISI into the cathodal-first stimulation waveform is to reduce the threshold strength of the following anodal stimulation. 47 However, to guarantee the safety of stimulation, the interval between cathodal and anodal stimuli cannot be too large.…”
Section: Discussionmentioning
confidence: 99%
“… 47 The aim of adding ISI into the cathodal-first stimulation waveform is to reduce the threshold strength of the following anodal stimulation. 47 However, to guarantee the safety of stimulation, the interval between cathodal and anodal stimuli cannot be too large. Therefore, choosing an appropriate duration of ISI is vital to improve the effect of cathodal-first stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the search for natural biomaterials, researchers have investigated the individual components of the ECM as platforms. Many biomaterials for scaffold construction, such as collagen, fibrinogen, silk, alginate, and chitosan, are under investigation [ 53 , 93 , 94 , 95 , 96 ].…”
Section: Materials Used For Artificial Scaffold Constructionmentioning
confidence: 99%
“…Even though they are not exclusive to collagen, cardiac patches have unique properties. One such feature is their potential to cultivate cells ex vivo to promote proper invasion of the patch; further, these patches can go into models and have high engraftment levels [ 93 ]. Lastly, a 3D collagen type I matrix seeded with autologous bone marrow mononuclear cells (for the regeneration of ischemic myocardium) showed increased thickness of the infarct scar with viable tissue and helped normalize cardiac wall stress in injured regions, limiting ventricular remodeling and improving diastolic function [ 103 ].…”
Section: Materials Used For Artificial Scaffold Constructionmentioning
confidence: 99%
See 1 more Smart Citation